2020
DOI: 10.47678/cjhe.vi0.188815
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status and Help-Seeking Strategies of Canadian International Students

Abstract: International students are at heightened risk of developing psychological distress, yet little research has been conducted on  their mental health or support needs. This quantitative study focused on undergraduate students at two mid-sized universities in Manitoba, Canada. Online and paper surveys were completed by 932 participants, of whom 21% identified as international students. This paper, descriptive in nature, outlines the sociodemographic profiles, current mental health status, psychological characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Shadowen and colleagues (2019) suggest that language barriers may in-tensify acculturative stress; barriers in communication may impede participation in class lectures, assignment quality, and creation of positive social connections with domestic students, as well as hinder help-seeking. Of interest, international students in our 2018 study were more likely to report flourishing mental health but less likely to talk about their hardships than domestic respondents (de Moissac et al, 2020). Although other studies have gathered information on the mental health of international students attending post-secondary education (Clough et al, 2018;Huang & Mussap, 2018;Shadowen et al, 2019), few have investigated the perception of belongingness and campus climate for students of diverse linguistic backgrounds in a minority setting.…”
Section: Post-secondary Institutions In Official Language Minority Communitiesmentioning
confidence: 74%
“…Shadowen and colleagues (2019) suggest that language barriers may in-tensify acculturative stress; barriers in communication may impede participation in class lectures, assignment quality, and creation of positive social connections with domestic students, as well as hinder help-seeking. Of interest, international students in our 2018 study were more likely to report flourishing mental health but less likely to talk about their hardships than domestic respondents (de Moissac et al, 2020). Although other studies have gathered information on the mental health of international students attending post-secondary education (Clough et al, 2018;Huang & Mussap, 2018;Shadowen et al, 2019), few have investigated the perception of belongingness and campus climate for students of diverse linguistic backgrounds in a minority setting.…”
Section: Post-secondary Institutions In Official Language Minority Communitiesmentioning
confidence: 74%
“…Some participants shared that their mental well-being improved when they felt they belonged in the institution. Belonging is a protective factor for post-secondary students' mental health (Benson & Whitson, 2021;de Moissac et al, 2019;Gopalan et al, 2022;Moeller et al, 2020). Penner et al (2021) noted that a sense of belonging might be increased among minority and culturally diverse student populations through targeted courses, use of a reflection, and connections with others.…”
Section: Discussionmentioning
confidence: 99%
“…Students benefit from a sense of belonging to an institution for a variety of reasons. Belonging appears to play a protective function related to mental health issues, which are more salient for post-secondary students (de Moissac et al, 2019;Moeller et al, 2020). A welcoming social environment and a sense of community may play protective roles and assist students in coping with feelings such as stress (Benson & Whitson, 2021), as well as depression and anxiety (Gopalan et al, 2022).…”
Section: Belonging In Post-secondary Educationmentioning
confidence: 99%
“…A prior systematic review of IS concluded that student mental health services might be of heightened yield in reducing impairment and suicide rates (Zhang & Goodson, 2011). Furthermore, most of these IS are unwillingly seeking psychological help due to poor awareness of health service availability and the cultural stigma (Eisenberg et al, 2007;Zhang & Dixon, 2003;Li et al, 2016;Han et al, 2013;Eisenberg et al, 2009;de Moissac et al, 2020), which could be challenges for both students and psychological professionals. The cultural-tailored clinical impactions and services are in need.…”
Section: Suicide In College Studentsmentioning
confidence: 99%